Solution of Riccati equation - Kostas Ramutis Petrauskas; Ignas Skučas; Irena Petrauskienė; Antanas Būda (Lietuvos Matematikos Rinkinys)
An analytical expression of general solution of Riccati equation is received. An analytical expression of general solution of second-order differential linear equation is received by solving Riccati equation.